"Klasik" glasbe 20. stoletja - vprašanje modernega in tradicionalnega v opusu Uroša Kreka - Pompe, Gregor (Muzikološki zbornik, 2010)
The article tries to resolve the questions raised in the course of investigating of Uroš Krek's work. The seeming discrepancy between the high aesthetic value of his works and the indifference towards inovation is solved with the help of the designation "the Slovenian classic of 20th century music". The designation has receptional value, but assumes also historical and local determinants.
Keywords: 20.st.; 20th century; Krek, Uroš, 1922-2008; Slovenian music; slovenska glasba